The proud prime evil of Hell - Hazemali, David (ELOPE (Ljubljana), 2016)
This paper looks into the characterisation of Satan as the Capital Vice of Pride in John Milton's Paradise Lost. It thus supports the findings of Robert Charles Fox, who in his study The Seven Deadly Sins in Paradise Lost first thoroughly analysed and comprehensively presented this issue and its importance in Milton's epic. The authors of the study share Fox's belief that Milton consciously used the system of the Seven Capital Vices in his epic as a structural device to present the entire scope of evil to the willing reader, and he achieved this by giving Satan and six other major denizens of Hell each the characteristics of a particular Vice. In other words, each of the seven major diabolical figures that appear in Paradise Lost embodies or personifies one of the Seven Capital Vices. As the most eloquent and characteristically perfected of the diabolical figures of Hell, Satan embodies Pride, the prime Capital Vice.
Keywords: angleška književnost; angleška poezija; literarne študije; Milton, John, 1608-1674; napuh; Satan; sedem naglavnih pregreh